2010
DOI: 10.1111/j.1439-0396.2008.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of humic substances supplementation provided through drinking water on performance, carcass traits and meat quality of broilers

Abstract: The present study aimed at evaluating the effects of different doses of humic substances (HS) in waterer pan on broiler performances and meat quality. For the trial, 480 chicks (ROSS 308) were allocated into four groups (HS0, HS150, HS300 and HS450) of 120 equally mixed-sex birds, each receiving a drinking water supplemented with 0, 150, 300 and 450 ppm of a humic acid (provided by 0.0%, 0.5%, 1.0% and 1.5% of HS, v/v) respectively. At the age of 21 and 42 days, feed consumption and live weight were taken. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
60
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 36 publications
15
60
0
6
Order By: Relevance
“…v pokusných skupín bola vyššia, avšak nebol zaznamenaný štatisticky významný rozdiel (P≥0,05) v porovnaní ku kontrolnej skupine. Podobne ako výsledky mnohých vedcov (Ozturk et al, 2010, Stanacév et al, 2011, Nagaraju et al 2014) aj výsledky tohto experimentu naznačujú, že humínové kyseliny, či už v čistej forme alebo v kombinácii s inými rastlinnými doplnkami by mohli byť jednou z alternatívnych náhrad kŕmnych antibiotík.…”
Section: Detailný Abstraktunclassified
See 1 more Smart Citation
“…v pokusných skupín bola vyššia, avšak nebol zaznamenaný štatisticky významný rozdiel (P≥0,05) v porovnaní ku kontrolnej skupine. Podobne ako výsledky mnohých vedcov (Ozturk et al, 2010, Stanacév et al, 2011, Nagaraju et al 2014) aj výsledky tohto experimentu naznačujú, že humínové kyseliny, či už v čistej forme alebo v kombinácii s inými rastlinnými doplnkami by mohli byť jednou z alternatívnych náhrad kŕmnych antibiotík.…”
Section: Detailný Abstraktunclassified
“…Humic acids are the most active substances with antioxidant effect (Vašková et al, 2011). Humic acids have a positive impact on meat quality, increasing weight gains and improve the immune system of broiler chickens (Ozturk et al, 2010;Nagaraju et al, 2014). The other alternatives to antibiotics as growth promoters are phytogenic feed additives (Puvača, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of exogenous enzymes in poor nutrient sources may ensure effective release and assimilation of nutrients and minerals in the gut, stimulating efficient nutrient utilization and, more importantly, promoting active bone growth (Ozturk et al, 2010;Kim et al, 2017). On the other hand, organic acids, including humic acids, have variable physical and chemical properties that allow them to influence gastronomic functions of feed in poultry.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that responses to alternatives to antibiotic growth promoters may be greater in a more challenging environment (Ozturk et al, 2010(Ozturk et al, , 2012 b Mineral premix supplied the following per kg: manganese, 120 g; zinc, 100 g; iron, 120 g; copper, 10-15 g; iodine, 0.7 g; selenium, 0.4 g; and cobalt, 0.2 g (Nutra Blend LLC, Neosho, MO 64850).…”
Section: Discussionmentioning
confidence: 99%